Impact of biological sex and gender-related factors on public engagement in protective health behaviours during the COVID-19 pandemic: cross-sectional analyses from a global survey. Issue 6 (10th June 2022) - Dev, Rubee; Raparelli, Valeria; Bacon, Simon L; Lavoie, Kim L; Pilote, Louise; Norris, Colleen M
Abstract : Objective: Given the role of sociocultural gender in shaping human behaviours, the main objective of this study was to examine whether sex and gender-related factors were associated with the public's adherence to COVID-19-recommended protective health behaviours. Design: This was a retrospective analysis of the survey that captured data on people's awareness, attitudes and behaviours as they relate to the COVID-19 policies. Setting: Data from the International COVID-19 Awareness and Responses Evaluation survey collected between March 2020 and February 2021 from 175 countries. Participants: Convenience sample around the world. Main outcome measures: We examined the role of sex and gender-related factors in relation to non-adherence of protective health behaviours including: (1) hand washing; (2) mask wearing; and (3) physical distancing. Multivariable logistic regression was conducted to determine the factors associated with non-adherence to behaviours. Results: Among 48 668 respondents (mean age: 43 years; 71% female), 98.3% adopted hand washing, 68.5% mask wearing and 76.9% physical distancing. Compared with males, females were more likely to adopt hand washing (OR=1.97, 95% CI: 1.71 to 2.28) and maintain physical distancing (OR=1.28, 95% CI: 1.22 to 1.34). However, in multivariable sex-stratified models, females in countries with higher Gender Inequality Indexes (GII) were less likely to report hand washing (adjusted OR (aOR)=0.47, 95% CI: 0.21 to 1.05). Females who reported being employed (aOR=0.22, 95% CI: 0.10 to 0.48) and in countries with low/medium GIIs (aOR=0.18, 95% CI 0.06 to 0.51) were less likely to report mask wearing. Females who reported being employed were less likely to report physical distancing (aOR=0.39, 95% CI: 0.32 to 0.49). Conclusion: While females showed greater adherence to COVID-19 protective health behaviours, gender-related factors, including employment status and high country-wide gender inequality, were independently associated with non-adherence. These findings may inform public health and vaccination policies in current as well as future pandemics.